Antibiotic resistance pattern of Extended-Spectrum ?-Lactamase (ESBL) producing Escherichia coli isolated from broiler farm environment in Pasuruan district, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yanestria SM, Dameanti FNAEP, Musayannah BG, Pratama JWA, Witaningrum AM, Effendi MH, Ugbo EN. 2022. Antibiotic resistance pattern of Extended-Spectrum ?-Lactamase (ESBL) producing Escherichia coli isolated from broiler farm environment in Pasuruan district, Indonesia. Biodiversitas 23: 4460-4465. Escherichia coli is one of the bacteria that can be used as an indicator of environmental pollution. This bacterium has the ability to become an antimicrobial-resistant bacterium that impacts public health. The antimicrobial ability can develop into a bacterium that produces extended-spectrum ?-lactamase (ESBL). The purpose of this study was to reveal the occurrence of extended-spectrum ?-lactamase (ESBL) producing E. coli from a broiler farm environment in Pasuruan district and to describe the phenotypic pattern of E. coli producing ESBL that has been detected. A total of 175 samples were used in this study consisting of 115 samples of coop swabs and 65 samples of wastewater around the farm. The samples were isolated and identified to find E. coli by using different culture media viz. McConkey agar (MCA), eosin methylene blue agar (EMBA), Gram staining, indole test, methyl red Voges Proskauer (MR-VP), citrate, and triple sugar iron agar (TSIA). Detection of ESBL using the double disc synergy test (DDST) according to standard Clinical and Laboratory Standards Institute procedures and the VITEK®2 compact apparatus. The results of ESBL confirmation with DDST and VITEK®2 showed that 16 (9.14%) of the 175 environmental samples confirmed E. coli produced ESBL. The results of the VITEK®2 test also produced a phenotypic pattern of resistance properties of ESBL-producing E. coli and found 12 types of resistance patterns. The combination of “AM AMP ATM KZ CTX CRO CIP” and “AM AMP ATM KZ CTX CRO GM CIP SXT” are the 2 most common resistance patterns (18.75%), while the other 10 resistance patterns occur at the same level (6.25%). The data presented here confirmed the presence of ESBL-producing E. coli in the farm environment, which can contribute to the dissemination of MDR bacteria in the environment if not monitored. Therefore, the presence of ESBL-producing E. coli in Pasuruan is worrisome since it can lead to an impact on human health.
Keywords: Escherichia coli, ESBL, public health, resistance patterns, VITEK®2 test